Implementing an Energy Management System: Initial Outcomes and Learnt Lessons - Lazarevska A. M., Mladenovska D (My University, 2017)
As a globally accepted framework for managing energy, the Energy Management System (EnMS) in line with ISO 50001 provides technical and management strategies for companies in terms of increasing energy efficiency, reducing costs and mitigating environmental impact. This paper focuses on the process of implementing the EnMS in line with ISO 50001 in the state owned Joint Stock Company (JSC) “Macedonian Power Plants”, Branch “Energetika”, within the timeframe of one year, identifies main barriers and drivers in terms of its successful implementation and elaborates the most significant findings/outcomes which contributed towards energy, thus cost savings, and related CO2 emission reductions. From the “soft” resources point of view, top management commitment, as well as, the existence of solid organizational hierarchy and good communication (both vertical and horizontal) are among the key priorities for efficient EnMS implementation. Professional skills, motivation and incentives of all involved employees with significant impact on the EnMS implementation are equally important. On the other side, the so called “hard” resources, i.e. the lack of process measurement, incorrect or obsolete measurement devices as well as problems with data availability are serious barriers in defining quantitative parameters and variables crucial for successful EnMS implementation, and proved to be a significant burden during determining viable energy savings targets.
Keywords: Energy Management System, energy management, energy efficiency, energy costs